Potential of urban health systems in climate response is being overlooked - Dora, Carlos; Loewenson, Rene; Obando, Francisco; Parnell, Susan (BMJ (Online), 2024)
Carlos Dora and colleagues argue that primary healthcare systems in cities are vital for creating resilient and equitable responses to climate change